Materi Pendidikan Anak dalam Islam (Studi Analisis Surah Luqman: 12-19) - Masri, Dedi; Salminawati, Salminawati; Amran, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This study aims to analyse: 1) children's education material in the Koran surah Luqman verses 12-19 and 2) the relevance of children's education material in the Koran surah Luqman verses 12-19 to current education. The research approach used in this research is qualitative research. This research concerns the concept of children's education in the Qur'an, so the approach used is the approach of education and the science of interpretation through the verses of the Qur'an. This research focuses on the Al-Qur'an surah Luqman, verses 12-19. The results of the research show that: 1) The educational material contained in the Koran, especially in Surah Luqman verses 12-19, basically includes three very fundamental things, namely: (a) education in aqidah/monotheism, namely not associating partners with Allah SWT and teaching that every action will be rewarded by Allah SWT. (b) sharia/worship education, namely the command to establish prayer and gratitude for the blessings of Allah SWT (c) moral education, namely serving parents, educating children not to be arrogant, and educating children to be civilised. 2) The relevance of Children's Education Materials in Al-Qur'an Surah Luqman Verses 12-19 to Current Education can be seen in the method of learning monotheism from an early age, by getting used to hearing the creed, teaching worship (such as prayer) ordered by religion by inviting children to do it, showering children with affection and teaching them to love others and the natural surroundings, and teaching children to serve their parents and respect their elders in words and deeds.